Responsible ChatGPT Use Among STKIP Muhammadiyah Pagaralam Students: Penggunaan ChatGPT yang Bertanggung Jawab di Kalangan Mahasiswa STKIP Muhammadiyah Pagaralam - Doan dimas; Yoga Pratama; Umi Kalsum (Academia Open, 2025)
General Background: The integration of artificial intelligence (AI) in education has transformed students' approaches to learning and task completion. Specific Background: One of the most prominent AI tools, ChatGPT, offers rapid assistance with academic work, yet raises concerns about over-reliance and ethical misuse. Knowledge Gap: Despite growing global discourse, there remains limited empirical research on AI usage in smaller, non-urban institutions in Indonesia. Aims: This study investigates how students at STKIP Muhammadiyah Pagaralam utilize ChatGPT to complete assignments, examining usage patterns, benefits, ethical awareness, and dependence. Results: Based on responses from 353 students, 95.8% reported using ChatGPT, primarily for essays and reference gathering. While 92.8% found it helpful for efficiency, 91.1% cross-verified its content, and 61.2% claimed continued task capability without it. Novelty: Unlike prior studies with conceptual or qualitative scopes, this research provides the first quantitative insight into ChatGPT's academic role in a Muhammadiyah institution. Implications: The findings highlight a balanced integration of AI, underscoring the need for institutional policies that encourage ethical use while fostering digital literacy and independent learning. Highlight : ChatGPT is widely used (95.8%) but students remain critical—91.1% verify its outputs with other sources. Most students benefit from faster task completion and improved understanding without over-relying on the tool. Ethical awareness is high—83.4% recognize plagiarism risks and support responsible AI use in education. Keywords : ChatGPT, Artificial Intelligence, Academic Tasks, Technology Dependence, Academic Ethics